Grazing, goods and girth: determinants and effects - Daniel S. Hamermesh (Institute for the Study of Labor (IZA), 2009)
Using the 2006-07 American Time Use Survey and its Eating and Health Module, I show that over half of adult Americans report grazing (secondary eating/drinking) on a typical day, with grazing time almost equaling primary eating/drinking time. An economic model predicts that higher wage rates (price of time) will lead to substitution of grazing for primary eating/drinking, especially by raising the number of grazing incidents relative to meals. This prediction is confirmed in these data. Eating meals more frequently is associated with lower BMI and better self-reported health, as is grazing more frequently. Food purchases are positively related to time spent eating - substitution of goods for time is difficult - but are lower when eating time is spread over more meals.
Keywords: J10; 330; Time use; BMI; household production; Gesundheitsvorsorge; Ernährungsgewohnheit; Gesundheitsrisiko; Einkommen; Zeit; USA